Venture Capital Impairments and Their Impact on Indonesia’s Startup Ecosystem - Ibnu Hamdan; Muhammad Tajuddin (LifeSciFi, 2024)
SoftBank's significant venture capital investments have played a crucial role in shaping Indonesia's startup ecosystem, enabling rapid business expansion and technological advancements. However, recent investment impairments have raised concerns regarding sustainability and long-term viability. This study explores the causes and consequences of SoftBank's portfolio impairments, examining both external factors such as market volatility, regulatory uncertainties, and shifting consumer preferences, as well as internal issues like weak business models and inefficient financial management. The findings indicate that these impairments not only affect investors but also pose financial and operational challenges for startups reliant on continuous funding. In response, strategic measures such as risk diversification, improved governance, and adaptive business models are essential for mitigating the negative impacts. Additionally, investors must adopt more rigorous due diligence processes, while startups should enhance financial transparency and innovation strategies. Policymakers also play a key role in establishing a stable investment climate. By addressing these challenges, stakeholders can foster a more resilient and sustainable startup ecosystem in Indonesia.